PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING PADA USAHA AMPLANG UD. TAUFIK JAYA MAKMUR DI SAMARINDA - Muhammad Ramadhani (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Determination of cost of goods must be applied appropriately and careful, because this can help entrepreneurs to compete in a manner well and in a relatively long period of time. The purpose of this study was to determine the calculation of the cost of production of the UD Taufik Jaya Makmur Samarinda Samarinda business which is used today and the calculation of the cost of production in the UD Taufik Jaya Makmur Samarinda Samarinda business according to the full costing method. Full costing is a method of determining the cost of production that takes into account all elements of production costs into the cost of production, which consists of the cost of raw materials, direct labor costs, and factory overhead costs, both behaving variable and fixed. The method used in this research is descriptive research with a quantitative approach. The variables of this study include the cost of production using the full costing method. Data analysis was performed by calculating the cost of production based on the concept of the full costing method. The results showed that the results of the analysis of the calculation of the Cost of Production of envelopes per kg in the UD Taufik Jaya Makmur Samarinda Endeavor conducted at present were Rp. 80,312.50 per kg. Whereas the Cost of Production of envelopes per kg in the UD Taufik Jaya Makmur Samarinda Business in Samarinda if calculated using the full costing method is Rp 83,068.23 per kg. The difference in cost of production of the UD Taufik Jaya Makmur Samarinda Amplang Business conducted so far using the full costing method for the UD Taufik Jaya Makmur Samarinda Endeavor is Rp 2,755.73 per kg. It is recommended that UD Taufik Jaya Makmur in Samarinda should calculate and charge all elements of the factory overhead costs in one production period (month). This is done so that information about the cost of production can be a good basis for the factory in setting the selling price of envelopes at UD Taufik Jaya Makmur in Samarinda.